Volatilitas Abnormal Saham BEI Pasca-Rebalancing MSCI - Siti Shoimatul Azizah; Sholehatul Inayah; Kholifatan Nisa (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The quarterly MSCI index rebalancing triggered massive foreign flows to the IDX (US$247 million per inclusion event) as global ETFs were required to adjust their portfolios. The IDX's low free float (25%) and reliance on foreign flows for 40% of daily transactions created extreme volatility. The trading halt in March 2025 (-5%, post-rebalancing) and the MSCI freeze on January 27, 2026 (JCI -8%, trading halt at 1:43 PM WIB) are evidence of a systemic phenomenon. The objectives of this study are: (1) To measure the impact of MSCI rebalancing on stock volatility; (2) To identify the differences between inclusion and exclusion; (3) To identify the determinants of volatility. The research method used an integrated GARCH(1,1) event study on 40 LQ45/IDX30 stocks from 20 rebalancing events from 2020-2025 (February, May, August, and November). Secondary data was used from Yahoo Finance's daily prices, official MSCI announcements, and IDX foreign flow. Estimation window (-120/-21 days), event window (-10/+20 days), paired t-test, fixed effects panel regression. The MSCI announcement caused stock volatility to increase 46% (from 1.45% to 2.12% daily) due to simultaneous buying/selling by foreign ETFs. Stocks included in the index (such as BREN +244%, BBRI inflow $320 million) were more volatile than stocks excluded (KLBF -5.3% panic selling). GARCH shows the effect persisted for 20+ days—not just 1-2 days. Panel regression evidence shows that volume increased 42% (β=0.58), and the weak rupiah (β=0.33) exacerbated the volatility, while large-cap stocks (BBCA) were more stable (β=-0.24).